ETHNOMATEMATICS ON CABBAGE CULTIVATION PATTERN - Hana Puspita Eka Firdaus; Yoga Dwi Windy Kusuma Ningtyas (AdMathEduSt: Jurnal Ilmiah Mahasiswa Pendidikan Matematika, 2022)
In the people of South Jember, especially in Wuluhan District, activities that cannot be separated from mathematics are buying and selling, farming and building houses. One of the interesting activities that also use mathematics in the field of agriculture, namely the determination of cabbage planting patterns. Based on the results of interviews with cabbage farmers in Wuluhan District, the cabbage planting pattern is regulated by pay attention of sunlight, irrigation, and ease of maintenance. So that there is a size and distance that must be regulated on the land when planting cabbage. This type of research is qualitative. Data collection technique used are observation, interviews, and documentation. This study was analyzed using the Nasution Circular model namely by reducing data, displaying data, and drawing conclusions. The results of this study are (1) the line spacing used is at least 60 cm; (2) the minimum distance between cabbage is 50 cm; (3) the cabbage planting hallway at least 80 cm; and (4) the distance of the cabbage plant from the edge of the land at least 60 cm. The distance is determined and is used by farmers as a condition for the cabbage plant can grow optimally. The size is determined by considering irrigation factors, ease of maintenance, and maximization of fertilizer absorption.